Raton's future in balance Economy may hinge on trade route ruling (Albuequerque, New Mexico Journal North, 2001)
Newspaper article on the possibility of rerouting traveler from Texas to Denver while bypassing New Mexico and the impact that would have on New Mexico Financial loss.
Master list item #: 16
File location is in the Raton file Cabinet
Keywords: Fissel, Kelly; U.S. 87; Interstate 25; NAFTA; North American Free Trade Agreement; Local History; Life and Customs; Biography; Highway; Financial impact; Tourist; Rerouting; Laredo, Texas; Raton, New Mexico; Denver, Colorado; Clayton, New Mexico; Oklahoma